IKHTILAF SAHABAT MENURUT SYAH WALIYULLAH AL-DAHLAWI DAN PENGARUHNYA TERHADAP PERKEMBANGAN IJTIHAD DALAM ASPEK HUKUM KELUARGA - M. . Ihsan (Hukum Islam, 2020)
AbstractThis article study abaut many causes the difference of sahabah’s views according to Syah Waliyulllah al-Dahlawi and its related to the defeloping of ijtihad in family law. The method that used in this article is library reseach. After researching is knewn  that the causes of differenfes of sahabah is caused the difference to judge and understand about the Tradition of Muhammad prophet, many verses of al-Quran has several meaning, difference of method using in understansing nash. Key words ; ikhtilaf sahabat, taklid, talfiq, hukum keluarga